Investigation of a historic masonry structure by numerical and operational modal analyses. (17th February 2015) - Nohutcu, H.; Demir, A.; Ercan, E.; Hokelekli, E.; Altintas, G.
Summary: This paper presents the results of model calibration conducted on a historical mosque called Hafsa Sultan in Manisa, Turkey. The finite element model of the mosque was calibrated by the use of the results obtained from ambient vibration tests of the structure. In order to develop a solid model of the structure, the dimensions of the structure, defects such as cracks and material degradations in the structure, and the materials used in different parts were identified. For the evaluation of the material properties of the structure, nondestructive and destructive testing methods were used. The numerical and experimental modal parameters of the structure were obtained by finite element method (FEM) and Operational Modal Analysis (OMA), respectively. The natural frequencies and corresponding mode shapes were obtained from both FEM and OMA and compared with each other. While a good compatibility was achieved between mode shapes, some differences between natural frequencies occurred. It was thought that the differences resulted from variations in the Young's modulus of masonry, cracks in elements or boundary conditions. Therefore, the finite element model was calibrated by changing material parameters. Finally, a more realistic numerical model of the mosque was put forward and the results were discussed in detail. Copyright © 2015 John Wiley & Sons, Ltd.